XRD Analysis of Ferrite Ceramics with Different Heat Treatment; Materials Science Forum; Vol. 970 : Modern Problems in Materials Processing, Manufacturing, Testing and Quality Assurance II - Surzhikov A. P. Anatoly Petrovich; Gyngazov (Ghyngazov) S. A. Sergey Anatolievich; Vlasov V. A. Vitaliy Anatolievich; Stary O. Oldrich; Sokolovskiy A. N. Alexey (2019, 2019)
Title screen